Magnetic Reconnection Inside a Flux Transfer Event‐Like Structure in Magnetopause Kelvin‐Helmholtz Waves. Issue 6 (7th June 2020) - Kieokaew, R.; Lavraud, B.; Foullon, C.; Toledo‐Redondo, S.; Fargette, N.; Hwang, K.‐J.; Malakit, K.; Ruffolo, D.; Øieroset, M.; Phan, T.‐D.; Hasegawa, H.; Fadanelli, S.; et al.
Abstract: Magnetopause Kelvin‐Helmholtz (KH) waves are believed to mediate solar wind plasma transport via small‐scale mechanisms. Vortex‐induced reconnection (VIR) was predicted in simulations and recently observed using NASA's Magnetospheric Multiscale (MMS) mission data. Flux Transfer Events (FTEs) produced by VIR at multiple locations along the periphery of KH waves were also predicted in simulations, but detailed observations were still lacking. Here we report MMS observations of an FTE‐type structure in a KH wave trailing edge during KH activity on 5 May 2017 on the dawnside flank magnetopause. The structure is characterized by (1) bipolar magnetic B Y variation with enhanced core field ( B Z ) and (2) enhanced total pressure with dominant magnetic pressure. The cross‐section size of the FTE is found to be consistent with vortex‐induced flux ropes predicted in the simulations. Unexpectedly, we observe an ion jet ( V Y ); electron parallel heating, ion, and electron density enhancements; and other signatures that can be interpreted as a reconnection exhaust at the FTE central current sheet. Moreover, pitch angle distributions of suprathermal electrons on either side of the current sheet show different properties, indicating different magnetic connectivities. This FTE‐type structure may thus alternatively be interpreted as two interlaced flux tubes with reconnection at the interface as reported by Kacem et al. (2018) and Øieroset et al. (2019s). The structure may be the result of interaction between two flux tubes, likely produced by multiple VIR at the KH wave trailing edge, and constitutes a new class of phenomenon induced by KH waves. Key Points: We present an MMS observation of a Flux Transfer Event‐type structure during a KH event on the dawn flank magnetopause beyond the terminator Its characteristics are consistent with a structure produced from multiple vortex‐induced reconnection X‐lines Reconnection signatures are found at the central current sheet while properties on either side indicate two flux tubes that interlace